Method for determining the bulk temperature of the acheson graphitization furnace core - Панов, Евгений Николаевич; Карвацкий, Антон Янович; Лелека, Сергей Владимирович; Лазарев, Тарас Валериевич; Педченко, Анатолий Юрьевич; Швачко, Денис Григорович (Eastern-European Journal of Enterprise Technologies, 2015)
In order to reduce energy consumption in graphitization of electrode products in Acheson furnaces, a method for rapid assessment of the bulk temperature of the furnace core, which is based on the furnace energy balance equation and takes into account active energy loss at the furnace entrance; heat loss from the core surface; heat loss and moisture evaporation; heat loss in the core booster gasification process was developed. The unknown coefficients of the method - the temperature dependences of the effective heat transfer coefficient from the core surface and the proportionality factor, which takes into account active energy loss in the direct core insulation heating, were determined by calculation using the verified numerical model of heat-electro-mechanical state of the Acheson furnace. Analysis of the results showed that the nature of temperature dependence of the proportionality coefficient, which takes into account active energy loss in the direct core insulation heating is similar to the temperature dependence of the specific electrical resistivity of the furnace core (core booster). Verification of the developed method showed good agreement with the numerical simulation results. The developed method was tested in conditions of the electrode manufacturer PJSC "Ukrgrafit", Ukraine and has allowed to reduce specific energy consumption while maintaining the necessary quality level of graphitized products.